Representaciones sociales entorno al territorio en la nación yanakuna, armenia, Quindío 2011 (2011)
The ethnographic research project Social Representations around the Territory of the Nation Yanakuna in Armenia, Quindío 2011, arose from the need of making visible risk situation of this community in relation to the Territory, from identifying the social representations of the same , consistent with their ancestral cosmology, their urban context and ethnic rights. The Minga of thought, semi-structured interviewsand, participant observation, served as methodological tools to investigate in depth the meanings of their own territory. Thus, the research process revealed as the Territory is deeply linked to indigenous cultural survival as well as being a pillar in the process of reindigenciacion that since 1970 was envision the metaphor: “The Reconstruction of the Home Yanakuna”. Although the urban context is a hostile environment for the full development of their cosmogony, the Yanakunas authorities recognize the sentence AUTO 004 of 2009 issued by the Constitutional Court of Colombia as a Order, as a tool for the enforcement of their ethnic rights to the territory which guarantees the Right to Self-Determination, exercising their territoriality according ancestral principles that today are fighting to preserve.